2012
DOI: 10.5051/jpis.2012.42.6.231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crown-to-implant ratio on periimplant marginal bone loss in the posterior region: a five-year retrospective study

Abstract: PurposeThe aim of this study was to evaluate the influence of the crown-to-implant (C/I) ratio on the change in marginal bone level around the implant and to determine the site-related factors influencing the relationship between the C/I ratio and periimplant marginal bone loss.MethodsA total of 259 implants from 175 patients were evaluated at a mean follow-up of five years. Implants were divided into two groups according to their C/I ratios: ≤1, and >1. Site-related factors having an influence on the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 15 publications
0
32
1
7
Order By: Relevance
“…Forty‐four of the articles were excluded from the present study by not accomplishing the inclusion criteria as depicted in Figure 2. Only 13 articles were included in this systematic review 10‐13,15,16,27‐33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty‐four of the articles were excluded from the present study by not accomplishing the inclusion criteria as depicted in Figure 2. Only 13 articles were included in this systematic review 10‐13,15,16,27‐33 …”
Section: Resultsmentioning
confidence: 99%
“…Over the years, several publications reported the C/I ratios of their implant‐supported prosthesis 10‐12 . However, although some authors reported the anatomic C/I ratio, 13,14 others showed the clinical C/I ratio 15,16 . Although the clinical C/I ratio seems to describe a more realistic biomechanical scenario, 17 the anatomic C/I ratio is most commonly found in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Misch 23 revealed that a C/I ratio of 0.5 to 1.0 reduces stress on the MBL, thereby preventing bone loss. Lee et al 19 revealed that implants with a C/I ratio below 1 exhibited greater peri-implant MBL than implants with a C/I ratio more than 1. Contrarily, Tawil et al 24 reported that C/I ratio did not prove to be a major biomechanical risk factor, as long as the occlusion is properly adjusted and occlusal contacts are placed as closely as possible to the emerging axis of the implant.…”
Section: Discussionmentioning
confidence: 98%
“…Da mesma forma que ocorre uma preocupação em relação à proporção desfavorável coroa-raiz em restaurações de coroa unitária, também existe um certo receio em relação à biomecânica das próteses implantossuportadas de peça única (VERRI et al, 2014). Uma proporção desfavorável coroa-implante (>1:1) poderia mostrar uma desvantagem biomecânica ao longo dos anos, uma vez que tais implantes podem ser menos resistentes a forças oclusais oblíquas, provocando aumento da tensão no tecido ósseo e componentes protéticos (NISSAN et al, 2011;LEE et al, 2012;VERRI et al, 2014;MORAES et al, 2015). O aumento da força oclusal pode causar perda óssea, fratura da porcelana, afrouxamento do parafuso dos pilares ou descimentação ou fratura dos componentes e até a perda da osseointegração (BLANES et al, 2007;BAYRAKTAR et al, 2013;VERRI et al, 2014).…”
Section: Implantes Dentários E Prótese Sobre Implantesunclassified